Definitely maybe not a detective : a novel - Fox, Sarah (Mystery writer) ([Wyatt Investigations mystery series], 2026)
"Emersyn Gray is definitely not a detective. Really, she's an unemployed twenty-eight-year-old raising her beloved niece in the only place she can afford after her ex-boyfriend ran off with her life savings: a run-down, seniors-only apartment complex that was desperatefor tenants. But never fear--her wild best friend has the perfect plan to get Emersyn back on her feet and stick it to her thieving ex:scare him into returning her money by hiring a private investigatorto prove he stole it. Only, there won't be an actual detective, just a fabricated business card from Wyatt Investigations--and a ridiculously hot stranger, who steps in to play the part--a stranger whosename is, coincidentally, Wyatt. Emersyn can't help but notice the real-life Wyatt is capital H-O-T hot, even though she's wary of his intentions. But her ex does seem flustered, and if she can get her money back and regain control of her life, maybe it'll finally prove to her parents that she can be a responsible caregiver to her niece. But the day after they set their plan in motion, the superintendent of Emersyn's apartment building winds up dead, and her neighbors turn to her fake detective agency for help after finding one of the phony business cards"--